Identification of Sleep Medicine and Anesthesia Core Topics for Anesthesia Residency: A Modified Delphi Technique Survey. (14th April 2021) - Berezin, Linor; Nagappa, Mahesh; Wong, Jean; Clivatti, Jefferson; Singh, Mandeep; Auckley, Dennis; Charchaflieh, Jean G.; Jonsson Fagerlund, Malin; Gali, Bhargavi; Joshi, Girish P.; Overdyk, Frank J.; Margarson, Michael; et al.
Abstract : BACKGROUND: Sleep disorders affect up to 25% of the general population and are associated with increased risk of adverse perioperative events. The key sleep medicine topics that are most important for the practice of anesthesiology have not been well-defined. The objective of this study was to determine the high-priority sleep medicine topics that should be included in the education of anesthesia residents based on the insight of experts in the fields of anesthesia and sleep medicine. METHODS: We conducted a prospective cross-sectional survey of experts in the fields of sleep medicine and anesthesia based on the Delphi technique to establish consensus on the sleep medicine topics that should be incorporated into anesthesia residency curricula. Consensus for inclusion of a topic was defined as >80% of all experts selecting "agree" or "strongly agree" on a 5-point Likert scale. Responses to the survey questions were analyzed with descriptive statistical methods and presented as percentages or weighted mean values with standard deviations (SD) for Likert scale data. RESULTS: The topics that were found to have 100% agreement among experts were the influence of opioids and anesthetics on control of breathing and upper airway obstruction; potential interactions of wake-promoting/hypnotic medications with anesthetic agents; effects of sleep and anesthesia on upper airway patency; and anesthetic management of sleep apnea. Less than 80% agreement was found for topics on the anesthetic implications of other sleep disorders and future pathways in sleep medicine and anesthesia. CONCLUSIONS: We identify key topics of sleep medicine that can be included in the future design of anesthesia residency training curricula.